Muscular power (upper and lower body) and performance in the hammer throw - Cook, Meagan K. (My University, 2006)
The relationship between upper body power, lower body power, and performance in the hammer throw was studied. At a late season NCAA track and field meet, nine athletes from Division III universities, with at least one year of experience in throwing the hammer, were the subjects for this research. Within one hour after each of the subjects completed all their competitions for the day, including the hammer throw, they performed the standard Wingate test on a Monarch cycle ergometer and a modified Wingate test on a modified cycle ergometer to determine muscular power in both the lower and upper body respectively. Data was then analyzed in Microsoft Excel’s spreadsheet and software. A correlational analysis was completed to determine the relationship of the mean differences (within each gender grouping) between performance and PR, performance and R-total (standard and modified Wingate), performance and peak anaerobic power (W/kg) (standard and modified Wingate), and anaerobic capacity (W/kg) (standard and modified Wingate). Statistical levels of significance were determined at the 5% level. From the women’s results, correlations of statistical significance at the 5% level were found with performance and PR (0.977), performance and standard Wingate R-total (0.698), performance and standard Wingate Peak AnC (0.7003), and performance and standard Wingate Rel AnC (0.7666). Correlations were not significant between performance and all three modified Wingate results: R-total (0.2738), Peak AnC (0.3288), and Rel AnC (0.2875). From the men’s results, correlations of statistical significance at the 5% level were found with performance and PR (0.944), performance and standard Wingate R-total (0.804), performance and standard Wingate Peak AnC (0.6833), performance and standard Wingate Rel AnC (0.7666). The correlation of performance and modified Wingate R-total (0.580) was also statistically significant, but the relationship was weak. Correlations were not significant between performance and the remaining modified Wingate results: Peak AnC (0.4287) and Rel AnC (0.2161). The correlations between performance and R-total, Rel Peak AnP, and Rel AnC for the standard Wingate, were very strong for both the female and male subjects. The modified Wingate, upper body test, only moderately correlated performance to R-total for the male subjects. This study indicated that the desired power for throwing the hammer related strongly to lower body power. This tends to suggest that lower body power would be a better predictor of current performance, and that future performance would be greatly influenced by training the lower body for higher power outputs.
This file was last viewed in Adobe Reader 7.0
Keywords: Hammer throwing -- Physiological aspects; Muscle strength; Exercise tests; Hammer throwing -- Training